Implementasi pembelajaran berdiferensiasi dalam menulis sastra di sekolah menengah atas - Rufaidah, Desy; Ermawati, Ermawati; Utomo, Asep Purwo Yudi; Trisniawati, Trisniawati; Dermawan, Rusdian Noor; Widyarini, Th. Laksmi; Rahmawati, Suci; Khusna, Zana Ismaul (Universitas Mulawarman, 2025)
This study examines the planning and implementation of differentiated instruction in literary writing at the senior high school level. The primary focus is how teachers respond to students’ varying interests and learning styles during the instructional process, as these individual differences necessitate adaptive and responsive instructional planning. Using a descriptive qualitative approach with a multiple case study design, this research was conducted at two public senior high schools with distinct geographical and student characteristics. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results indicate that teachers conducted diagnostic assessments to identify students’ readiness, interests, and learning profiles, which served as the foundation for designing instructional modules. These modules incorporated content differentiation through varied examples of short stories and hikayat in both visual and audiovisual formats. Process differentiation was implemented by grouping students based on their interests and learning styles and by offering choices in writing themes. Furthermore, product differentiation allowed students to submit their work in either print or digital formats. The implementation of differentiated instruction demonstrates teachers’ efforts to create inclusive, engaging, and student-centered learning environments that effectively accommodate diverse learner needs.